1993
DOI: 10.1126/science.8424172
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Stimulation of Aerobic PCB Biodegradation in Hudson River Sediments

Abstract: A 73-day field study of in situ aerobic biodegradation of polychlorinated biphenyls (PCBs) in the Hudson River shows that indigenous aerobic microorganisms can degrade the lightly chlorinated PCBs present in these sediments. Addition of inorganic nutrients, biphenyl, and oxygen enhanced PCB biodegradation, as indicated both by a 37 to 55 percent loss of PCBs and by the production of chlorobenzoates, intermediates in the PCB biodegradation pathway. Repeated inoculation with a purified PCB-degrading bacterium fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(87 citation statements)
references
References 29 publications
3
84
0
Order By: Relevance
“…Thus, the primary advantage of PCB-growing strains is that the maintenance of an adequate PCB-degrading population should occur and would avoid either the repeated inoculation of strains into the contaminated site (12) or the use of a second carbon source to stimulate cometabolism, such as biphenyl (2,13), surfactants (20,21), or plant aromatic compounds (11). For this approach to be successful, however, the plasmid constructs must remain stable, which was the case over the course of our experiment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the primary advantage of PCB-growing strains is that the maintenance of an adequate PCB-degrading population should occur and would avoid either the repeated inoculation of strains into the contaminated site (12) or the use of a second carbon source to stimulate cometabolism, such as biphenyl (2,13), surfactants (20,21), or plant aromatic compounds (11). For this approach to be successful, however, the plasmid constructs must remain stable, which was the case over the course of our experiment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that a number of PCB-degrading bacteria are known, this pollutant is recalcitrant in the environment, and efforts at bioremediation with optimized strains were often not very successful (11). To improve intrinsic bioremediation, a passive remedial approach that depends on microbial processes to degrade and dissipate pollutants in soil and groundwater, one has to understand the influence of this highly hydrophobic substrate on the autochthonous microbial community.…”
mentioning
confidence: 99%
“…In addition, several projects, including one at DOE'S Savannah River Site, have demonstrated that TCE can be co-metabolically degraded in situ by providing methane as a carbon source. Explosives and polychlorinated biphenyls (PCBs) have been biodegraded in field-scale experiments (Harkness et al, 1993). Bacterial transformation and immobilization of trace metals such as selenium also have been implemented on a limited basis (Benson et al, 1993).…”
Section: B Ioremedia Tionmentioning
confidence: 99%